2007
DOI: 10.1177/1065912907305683
|View full text |Cite
|
Sign up to set email alerts
|

Experienced Advocates and Litigation Outcomes

Abstract: While the facts and the attendant law are essential components of understanding litigation outcomes, extralegal factors, such as the experience of the attorney representing each party, are also significantly related. The authors assert that the capability of the attorney, as evidenced in previous litigation success, is more significant than experience alone. They test this assertion for the South African appellate court from 1970 to 2000. After controlling for the effects of a number of variables, the results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…6 There may be an independent experience effect, for lawyer experience still has a (positive) effect on outcomes even when the quality of oral argumentation is taken into account (McAtee and McGuire, 2007). However, scholars who have proxied quality with win rates in prior cases have found that this nullifies the effect of experience (Haynie and Sill, 2007).…”
Section: Counselmentioning
confidence: 99%
See 1 more Smart Citation
“…6 There may be an independent experience effect, for lawyer experience still has a (positive) effect on outcomes even when the quality of oral argumentation is taken into account (McAtee and McGuire, 2007). However, scholars who have proxied quality with win rates in prior cases have found that this nullifies the effect of experience (Haynie and Sill, 2007).…”
Section: Counselmentioning
confidence: 99%
“…I should like to thank Haynie et al (2007) for making their data publicly available, and the anonymous reviewers for greatly improving the article by their comments and suggestions. I should also like to thank Daithí Mac Síthigh for his helpful comments and encouragement.…”
Section: Notesmentioning
confidence: 99%